2018
DOI: 10.1097/dcr.0000000000001041
|View full text |Cite
|
Sign up to set email alerts
|

Elective Stoma Reversal Has a Higher Incidence of Postoperative Clostridium Difficile Infection Compared With Elective Colectomy: An Analysis Using the American College of Surgeons National Surgical Quality Improvement Program and Targeted Colectomy Databases

Abstract: Patients who undergo elective stoma reversal have a higher incidence of postoperative C difficile infection compared with patients who undergo an elective colectomy. Given the impact of postoperative C difficile infection, a heightened sense of suspicion should be given to symptomatic patients after stoma reversal. See at Video Abstract at http://links.lww.com/DCR/A553.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Recently, a retrospective colectomy database review of the 2015 American College of Surgeons National Surgical Quality Improvement Project [102] demonstrated that stoma reversal (OR = 2.701, 95% CI 1.966–3.711; p < 0.001), smoking (OR = 1.520, 95% CI 1.063–2.174; p = 0.022), steroids (OR = 1.677, 95% CI 1.005–2.779; p = 0.048), and disseminated cancer (OR = 2.312, 95% CI 1.437–3.719; p = 0.001) were associated with CDI in the 30-day postoperative period.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Recently, a retrospective colectomy database review of the 2015 American College of Surgeons National Surgical Quality Improvement Project [102] demonstrated that stoma reversal (OR = 2.701, 95% CI 1.966–3.711; p < 0.001), smoking (OR = 1.520, 95% CI 1.063–2.174; p = 0.022), steroids (OR = 1.677, 95% CI 1.005–2.779; p = 0.048), and disseminated cancer (OR = 2.312, 95% CI 1.437–3.719; p = 0.001) were associated with CDI in the 30-day postoperative period.…”
Section: Risk Factorsmentioning
confidence: 99%
“…There are few cohort and case studies describing CDI following loop ileostomy reversal. Previous studies have reported incidence of up to 4%, 3,4 but a systematic review in 2017 found it to be less common at 1.8% 5 …”
Section: Figurementioning
confidence: 99%
“…For instance, the largest study of 2235 patients by Skancke et al observed a 3.04% incidence of CDI after ileostomy reversal versus 1.25% for elective colonic resection. 2 Similarly, Randall et al reported that the CDI rate was higher following ileostomy reversal (4.2%) compared with right hemicolectomy (2.1%) and anterior resection (1%). 4 Proposed mechanisms for this discrepancy in incidence of CDI following reversal of ileostomy compared with colonic resection include changes in the colonic microbiome due to diversion of faecal stream 7 as well as ileal CD colonization.…”
mentioning
confidence: 91%